D‐series resolvin attenuates vascular smooth muscle cell activation and neointimal hyperplasia following vascular injury. Issue 6 (13th February 2013) - Miyahara, Takuya; Runge, Sara; Chatterjee, Anuran; Chen, Mian; Mottola, Giorgio; Fitzgerald, Jonathan M.; Serhan, Charles N.; Conte, Michael S.
Abstract : Recent evidence suggests that specialized lipid mediators derived from polyunsaturated fatty acids control resolution of inflammation, but little is known about resolution pathways in vascular injury. We sought to determine the actions of D‐series resolvin (RvD) on vascular smooth muscle cell (VSMC) phenotype and vascular injury. Human VSMCs were treated with RvD1 and RvD2, and phenotype was assessed by proliferation, migration, monocyte adhesion, superoxide production, and gene expression assays. A rabbit model of arterial angioplasty with local delivery of RvD2 (10 nM vs. vehicle control) was employed to examine effects on vascular injury in vivo. Local generation of proresolving lipid mediators (LC‐MS/MS) and expression of RvD receptors in the vessel wall were assessed. RvD1 and RvD2 produced dose‐dependent inhibition of VSMC proliferation, migration, monocyte adhesion, superoxide production, and proinflammatory gene expression (IC50 ≈0.1–1 nM). In balloon‐injured rabbit arteries, cell proliferation (51%) and leukocyte recruitment (41%) were reduced at 3 d, and neointimal hyperplasia was attenuated (29%) at 28 d by RvD2. We demonstrate endogenous biosynthesis of proresolving lipid mediators and expression of receptors for RvD1 in the artery wall. RvDs broadly reduce VSMC responses and modulate vascular injury, suggesting that local activation of resolution mechanisms expedites vascular homeostasis.—Miyahara, T., Runge, S., Chatterjee, A., Chen, M., Mottola, G., Fitzgerald, J. M., Serhan, C. N., Conte, M. S. D‐series resolvin attenuates vascular smooth muscle cell activation and neointimal hyperplasia following vascular injury. FASEB J. 27, 2220–2232 (2013). www.fasebj.org